Altered zinc balance in the Atp7b−/− mouse reveals a mechanism of copper toxicity in Wilson disease. Issue 11 (2nd October 2018) - Meacham, Kelsey A.; Cortés, María Paz; Wiggins, Eve M.; Maass, Alejandro; Latorre, Mauricio; Ralle, Martina; Burkhead, Jason L.
Abstract : Copper accumulation in the Atp7b −/− model of Wilson disease impacts zinc distribution. Abstract : Wilson disease (WD) is an autosomal recessive disorder caused by mutation in the ATP7B gene that affects copper transport in the body. ATP7B mutation damages copper transporter function, ultimately resulting in excessive copper accumulation and subsequent toxicity in both the liver and brain. Mechanisms of copper toxicity, however, are not well defined. The Atp7b −/− mouse model is well-characterized and presents a hepatic phenotype consistent with WD. In this study, we found that the untreated Atp7b −/− mice accumulate approximately 2-fold excess hepatic zinc compared to the wild type. We used targeted transcriptomics and proteomics to analyze the molecular events associated with zinc and copper accumulation in the Atp7b −/− mouse liver. Altered gene expression of Zip5 and ZnT1 zinc transporters indicated a transcriptional homeostatic response, while increased copper/zinc ratios associated with high levels of metallothioneins 1 and 2, indicated altered Zn availability in cells. These data suggest that copper toxicity in Wilson disease includes effects on zinc-dependent proteins. Transcriptional network analysis of RNA-seq data reveals an interconnected network of transcriptional activators with over-representation of zinc-dependent and zinc-responsive transcription factors. In the context of previous research, these observations support the hypothesis that mechanisms of copper toxicity include disruption of intracellular zinc distribution in liver cells. The translational significance of this work lies in oral zinc supplementation in treatment for WD, which is thought to mediate protective effects through the induction of metallothionein synthesis in the intestine. This work indicates broader impacts of altered zinc-copper balance in WD, including global transcriptional responses and altered zinc balance in the liver.